Nutrition Fuels Human Capital : Ghana's School Feeding Programme - Global Delivery Initiative (Global Delivery Initiative, Washington, DC, 2020)
One important step in Ghana’s effort to develop its human capital was the Ghana School Feeding Programme (GSFP). This multi-sectoral program, initiated in 2005, had multiple objectives: it was a nutrition program, an education program, and a social safety net. Ghana also linked the program to agricultural development, especially smallholder production, thus helping to create new markets for locally grown food.